THE EFFECT OF FREE CASH FLOW, INVESTMENT OPPORTUNITY SET AND INSTITUTIONAL OWNERSHIP ON DIVIDEND POLICY - Demila Adliana Karmelia Putri; Khoirunisa Azzahra (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to determine the effect of free cash flow, investment opportunity set, and institutional ownership on dividend policy in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in the 2016-2020 period. This type of research is quantitative, the data used is secondary data in the form of financial reports obtained through the official website of the Indonesian Stock Exchange. The sample was selected by Purposive Sampling method and obtained sample of 7 companies with the total sample company is 35 units of analysis. The data analysis technique used is panel data regression analysis using the Eviews 10 program data processing. The results show that free cash flow, investment opportunity set and institutional ownership simultaneously have an effect on dividend policy in food and beverage sub-sector manufacturing companies listed on the IDX in 2016-2020. Meanwhile, partially free cash flow and investment opportunity set variables have no effect on dividend policy.